Influence of Canopy Pruning on Orange Growth and Rhizome Yield of Intercrop Ginger under Agri-Horticulture System. - Tabin, Tasso; Balasubramanian, D.; Arunachalam, A. (Indian Journal of Hill Farming, 2015)
A field experiment was conducted during 2010-2011 at farmer orchard to determine the influence of canopy pruning on productivity of orange tree and intercrop (ginger) under rainfed conditions at Geku, Arunachal Pradesh. The growth parameter (dhb, height and canopy diameter) of orange tree was significantly (P < 0.05) higher in control than different canopy pruning intensities (50 % and 70 %) in both the year. However, the rate of growth, number of fruit/tree and kg/tree was significantly higher in pruned trees than control (unpruned). The growth and yield of intercrop was also significantly higher in trees pruned at different canopy intensities than control. Among canopy pruning intensities, 50 % canopy pruning intensity had higher rate of growth (5.7 %), number of fruit/tree (50 numbers) and kg/tree (1.13 kg) of orange while control (unpruned) had decline result with 1.7 %, 0.06 numbers of fruit/tree and 0.05 kg/tree respectively. However, the growth and rhizome yield of ginger was increase significantly at 70 % canopy pruning higher than 50 % canopy pruning and control. However, there was decline in growth and yield at 70 % canopy pruning and control (unpruned) in the next cropping season except, for 50 % canopy pruning which increase significantly with 38.66 cm, 3.78 numbers and 72.20 g/plant.